Essential oils from the genus Thymus as antimicrobial food preservatives: Progress in their use as nanoemulsions-a new paradigm. (May 2021) - Pandey, Abhay K.; Chávez-González, Mónica L.; Silva, Ana Sanches; Singh, Pooja
Abstract: Background: The biodeterioration of food commodities by microbial pathogens remains a major public health concern. Worldwide, investigations have been carried out to develop harmless natural food preservatives based on essential oils (EOs) to protect food commodities, and advances have been made to meet users' acceptance as a substitute for synthetic preservatives. Scope and approach: In recent years, antimicrobial and antioxidant potential of the EOs from Thymus species have been documented with increasing demands from legislation changes, adaptation to the consumer trends, search for alternatives to solve rising food microbial pathogen resistance, and substitution of synthetic preservatives associated with adverse health effects. Hence, the present review paper emphasizes on the antimicrobial and antioxidant applications of EOs from different species of the genus Thymus and discloses the gaps where investigations are required. In addition, progress in the using Thymus EOs (TEOs) based nanoemulsions in food preservation, and their challenges in the application in food systems have also been discussed. Key findings and conclusions: TEOs are rich in pharmacologically active constituents that confirm their industrial and health applications. In addition, TEOs and their nanoemulsions not only provide themselves to exploit in the food industry, but are also put under GRAS (Generally Recognized As Safe) category, and have shown potential inhibitory activity against a broad range of pathogens in food commodities. Thus, TEOs can be a source for the development of natural preservatives that meet the needs of the food industry to satisfy both its requirements and those of the consumers. However, despite the potential for EOs, more studies are required to assess their probable side effects and safety levels before considering their deployment for food purposes. Graphical abstract: Image 1 Highlights: Biological activities of Thymus essential oils (TEOs) were reviewed. Microorganisms deteriorating foodstuffs were re-studied. Phytochemical properties of biologically active TEOs were explained. Exploitation of TEOs and their nanostructures in food preservation was discussed. Challenges in using TEOs in food systems were addressed.